2014
DOI: 10.1080/08952841.2014.854571
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological and Health Consequences of Caring for a Spouse With Dementia: A Critical Comparison of Husbands and Wives

Abstract: Caring for someone with dementia can be demanding, particularly for spouses living with the care recipient. The main goal of this study was to clarify differences in the experience of caregivers who were husbands and wives with respect to burden, health, healthy behaviors, presence of difficult care recipient behaviors, social supports, and the quality of the premorbid relationship. The results of this study support research demonstrating a difference between the caregiving experiences of women and men. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 68 publications
3
38
3
4
Order By: Relevance
“…The decision to care for a spouse is often driven by necessity, regardless of gender, and is therefore not always a voluntary act. Previous reports indicated that the experiences of spouses as caregivers could be distinct from those of adult children, with spouses experiencing more burden and depression than other family members Gibbons et al, 2014). In our study, we identified higher CBI scores in spouse caregivers than in children caregivers, but the difference was not statistically significant, indicating similar levels of burden.…”
Section: Discussioncontrasting
confidence: 59%
“…The decision to care for a spouse is often driven by necessity, regardless of gender, and is therefore not always a voluntary act. Previous reports indicated that the experiences of spouses as caregivers could be distinct from those of adult children, with spouses experiencing more burden and depression than other family members Gibbons et al, 2014). In our study, we identified higher CBI scores in spouse caregivers than in children caregivers, but the difference was not statistically significant, indicating similar levels of burden.…”
Section: Discussioncontrasting
confidence: 59%
“…Previous studies have also shown that there can be gender differences related to perceived caregiver burden. For example, female caregivers have experienced a greater caregiver burden and higher levels of depression than males (Gibbons et al, 2014;Perz, Ussher, Butow, & Wain, 2011;Pinquart & S€ orensen, 2006). An increased number of caregiving tasks and assisting the recipient with multiple activities of daily living have been associated with a greater perceived burden (Chan & Chui, 2011;Coleman et al, 2012;Kim et al, 2012;Savundranayagam, Montgomery, & Kosloski, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted health promotion may benefit female caregivers, who take part in fewer health promoting activities than men (Gibbons et al, 2014). For instance, one Spanish study showed that, although overall physical health of female caregivers caring for a person with dementia was similar to non-caregivers, the caregiver group smoked more and were more likely to classify themselves as being physically inactive (Gusi et al, 2009).…”
Section: Coping Strategiesmentioning
confidence: 99%
“…Views about traditional gendered cultural and societal expectations of the caregiver role assume women have a 'natural aptitude for caring' (Toepfer et al, 2014), and the desire to enhance the wellbeing of their family members (Ducharme et al, 2011), with differences between men and women caregivers highlighted in a number of studies (Papastavrou et al, 2007;Gibbons et al, 2014). A higher proportion of women (39%) than men (33%) report they had no choice in becoming an informal caregiver (Alzheimer's Association, 2014).…”
Section: Cultural Expectationsmentioning
confidence: 99%
See 1 more Smart Citation